Can shared E-scooters reduce CO2 emissions by substituting car trips in Germany?. (August 2022) - Gebhardt, Laura; Ehrenberger, Simone; Wolf, Christian; Cyganski, Rita
Highlights: E-scooters' car-trip substitution potential for e-scooters estimated on basis of based on German mobility data. 13 % of daily car trips or 2 % of vehicle-kilometers traveled suitable for replacement. Calculation of daily potential greenhouse gas reduction through by switching to e-scooters. Maximum savings of 1.2% of transportation GHG achievable if replacing gasoline cars. Savings highly dependent on use case; potentially negative for BEV-replacement potentially negative. Abstract: This paper explores which trips currently made in Germany by personal motorized transportation could be replaced by e-scooters and what effect this would have on greenhouse gas emissions. This potential for substitution is estimated on the basis of data from the national household travel survey in Germany. Our analysis shows that 13% of the daily car trips, corresponding to 2% of the car kilometers in Germany, are suitable for replacement. Based on these results, we show that saving potentials of greenhouse gas emissions are heavily dependent on the general conditions of the specific use case (e.g. e-scooter lifetime) and the type of vehicle replaced. At best, a saving potential of about 5.8 kt of CO2eq per day could be achieved when trips with conventional cars are replaced by e-scooter driving. However, if battery electric cars are replaced, an increase in emissions may even occur under certain conditions.